Communique of the 310th Meeting of the Peace and Security Council of the African Union (Tufts Archival Research Center, 2015)
This document is about the decision adopted by The Peace and Security Council of the African Union (AU) at its 310th meeting held on the status of negotiations between the Republic of Sudan and the Republic of South Sudan on their post_secession relations. The decisions include among others: stressing the concerns about unilateral actions by the two, expressing concerns about border demarcations, and calls on the international community to extend its support to the AUHIP.